2006
DOI: 10.1007/s00534-006-1113-5
|View full text |Cite
|
Sign up to set email alerts
|

Nodal involvement as an indicator of postoperative liver metastasis in carcinoma of the papilla of Vater

Abstract: because these variables are correlated with nodal involvement. However, our data revealed only the sites of the positive nodes, without addressing the effect of extended lymph node dissection and adjuvant chemotherapy. To date, there has been reporting of extended lymph node dissection and adjuvant chemotherapy in patients with carcinoma of the papilla of Vater. Further studies will be necessary to resolve these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Sakata et al reported that survival outcome was significantly worsened in the following order: patients with negative lymph node metastasis, patients with 1-3 metastatic lymph nodes, and patients with ≥ 4 metastatic regional nodes (16). Large tumor size (14,26), pancreatic invasion (5,24), ulcer formation and tumor differentiation (15), higher recurrent rate of liver metastasis following surgery (15) were significantly correlated with lymph node metastasis. The patients who had lymph node metastasis did not demonstrate significantly poorer survival in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sakata et al reported that survival outcome was significantly worsened in the following order: patients with negative lymph node metastasis, patients with 1-3 metastatic lymph nodes, and patients with ≥ 4 metastatic regional nodes (16). Large tumor size (14,26), pancreatic invasion (5,24), ulcer formation and tumor differentiation (15), higher recurrent rate of liver metastasis following surgery (15) were significantly correlated with lymph node metastasis. The patients who had lymph node metastasis did not demonstrate significantly poorer survival in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic ultrasound-guided fine-needle aspiration biopsy revealed adenocarcinoma of the duodenal papilla. Standard pancreaticoduodenectomy usually is the primary treatment for duodenal papilla carcinoma (28)(29)(30). However, considering the patient's age and poor performance status, a palliative endoscopic retrograde biliary stent placement drainage was performed to relieve his biliary obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of ampullary carcinoma is relatively better than that of other biliary tract cancers after surgical resection [10]. Lymph node metastasis and pancreatic invasion are important prognostic factors [4,11]. Beger et al [12] reported that lymph node involvement was observed in about 10% of patients with a pT1 carcinoma of the papilla.…”
Section: Discussionmentioning
confidence: 99%